Use of networks Petri for rational control of technological process - Кузовик, В. Д.; Іванець, О. Б. (Proceedings of National Aviation University (archive), 2003)
At this article was considered methodological approach to solution actual problem of optimum direction of tehnological process of production. At formal level was adduced algorithm construction this system of direction. The criterion of optimization for development of an optimum control system is determined. The original material concerning modeling process of management of technological process by networks Petri is given